KUASI NARASI, KUASA GRAMATIKA: STRATEGI INKLUSI VAN LEEUWEN DALAM PEMBERITAAN MAHASISWA TOLAK KENAIKAN HARGA BBM: Narrative Quality, Gramatic Power: Van Leeuwen's Inclusion Strategy in Student Reporting Rejecting The Increase of Fuel Price - Nanik Yuliana; Adi Syaiful Muchtar; Moh Atikurrahman (TOTOBUANG, 2023)
Abstract News narratives ideally provide credible and accurate information for the audience. The narrative construction of the news created by the mass media (online) should contain clear and non-taxical information. However, the fact that the media tends to use language in construction makes the information reported blurry and even distorted. The purpose of this qualitative research is to reveal the strategies and performances of actors (subjects) in two news narratives, â€œBEM SI Demo at the Ricuh Horse Statue, Students Break through Barbed Wireâ€ (idntimes.com) and â€œDemo Reject Fuel Increase at the Horse Statue Colored by Mutual Action. Pushâ€ (Tribunnews.com). The two objects will be studied using Theo Van Leeuwen's theory of discourse analysis, especially regarding the inclusion strategy, namely how a party or group is presented in the news narrative. The data collection technique was carried out with the technique of note-taking and free-to-talk, while the data analysis method used the Flow and Agih method. Based on the analysis that has been done, idntimes.com and Tribunnews.com use inclusion strategies in the form of differentiation, abstraction, and assimilation. In the news narrative, differentiation creates a contrasting effect on social actors, abstraction causes social actors and events to not appear clearly or abstractly, while assimilation makes social actors anonymous. Keywords: Theo Van Leeuwen's Discourse Analysis, rising fuel prices, inclusion strategy Â  Abstrak Narasi berita idealnya memberikan informasi yang kredibel dan akurat bagi khalayak pembaca. Dalam hal itu, konstruksi naratif pemberitaan yang diciptakan media massa (daring) idealnya memuat informasi yang jelas dan tidak taksa. Namun fakta media cenderung memainkan bahasa dalam kontruksi narasi membuat informasi yang diberitakan cenderung menjadi kabur dan terdistorsi. Tujuan penelitian kualitatif ini untuk mengungkap strategi dan penampilan aktor (subjek) pada dua narasi berita, â€œDemo BEM SI di Patung Kuda Ricuh, Mahasiswa Terobos Kawat Berduriâ€ (idntimes.com) dan â€œDemo Tolak Kenaikan BBM di Patung Kuda Diwarnai Aksi Saling Dorongâ€ (Tribunnews.com). Kedua objek tersebut akan dikaji menggunakan teori analisis wacana Theo Van Leeuwen khususnya tentang strategi inklusi, yaitu bagaimana suatu pihak atau kelompok ditampilkan dalam narasi berita. Teknik pengumpulan data dilakukan dengan teknik catat dan simak bebas libat cakap, sedangkan metode analisis data menggunakan metode Alir dan Agih. Berdasarkan analisis yang telah dilakukan, idntimes.com dan Tribunnews.com menggunakan strategi inklusi bentuk diferensiasi, abstraksi, dan asimilasi. Dalam dua narasi berita tersebut di atas, diferensiasi menimbulkan efek kontras mengenai aktor sosial; abstraksi menyebabkan aktor sosial dan peristiwa tidak tampil secara jelas alias kabur; sedangkan asimilasi membuat aktor sosial menjadi anonim.Kata Kunci: Analisis wacana, Theo Van Leeuwen, harga BBM, strategi, inklusi